Gender differences in characteristics and outcomes in heart failure patients referred for end‐stage treatment. (6th September 2021) - Fluschnik, Nina; Strangl, Felix; Kondziella, Christoph; Goßling, Alina; Becher, Peter Moritz; Schrage, Benedikt; Schnabel, Renate B.; Bernadyn, Julia; Bremer, Wiebke; Grahn, Hanno; Bernhardt, Alexander M.; Reichenspurner, Hermann; et al.
Abstract: Aims: Despite signals from clinical trials and mechanistic studies implying different resilience to heart failure (HF) depending on gender, the impact of gender on presentation and outcomes in patients with HF remains unclear. This study assessed the impact of gender on clinical presentation and outcomes in patients with HF referred to a specialised tertiary HF service. Methods and results: Consecutive patients with HF referred to a specialised tertiary HF service offering advanced therapy options including left ventricular assist devices (LVAD) and heart transplantation were prospectively enrolled from August 2015 until March 2018. We assessed clinical characteristics at baseline and performed survival analyses and age‐adjusted Cox regression analyses in men vs. women for all‐cause death and a combined disease‐related endpoint comprising death, heart transplantation, and LVAD implantation. Analyses were performed for the overall study population and for patients with HF with reduced ejection fraction (HFrEF). Of 356 patients included, 283 (79.5%) were male. The median age was 58 years (interquartile range 50–67). Two hundred and fifty‐one (74.5%) patients had HFrEF. HF aetiology, ejection fraction, functional status measures, and most of the cardiac and non‐cardiac comorbidities did not differ between men and women. In a median follow‐up of 3.2 years, 50 patients died (45 men, 5 women), 15 patients underwent LVAD implantation, and 8 patients heart transplantation. While all‐cause death was not significantly different between both genders in the overall population [16.9 vs. 6.0%, P  = 0.065, hazard ratio (HR) 2.29 (95% confidence interval 0.91–5.78), P  = 0.078], in the HFrEF subgroup, a significant difference between men and women was observed [20.7% vs. 3.9%, P  = 0.017, HR 3.67 (95% confidence interval 1.13–11.91), P  = 0.031]. The combined endpoint was more often reached in men than in women in both the overall population [21.6% vs. 9.0%, P  = 0.053, HR 2.51 (1.08–5.82), P  = 0.032] and the HFrEF subgroup [27.1% vs. 7.7%, P  = 0.015, HR 3.58 (1.29–9.94), P  = 0.014]. Conclusions: Patients referred to a specialised tertiary HF service showed a similar clinical profile without relevant gender differences. In the mid‐term follow‐up, more male than female patients died or underwent heart transplantation and LVAD implantation. These findings call for independent validation and for further research into gender‐specific drivers of HF progression.